Tradisi Mamose di Desa Topoyo Kecamatan Topoyo Kabupaten Mamuju Tengah: Studi Komparatif Hukum Islam dan Hukum Adat - Lestari, Ayu; Mustafa, Zulhasari (Shautuna: Jurnal Ilmiah Mahasiswa Perbandingan Mazhab, 2023)
The implementation of the mamose tradition maintains the value of togetherness between ordinary people and regional officials. Still, the question is what is the position of the mamose tradition in Topoyo village, Topoyo subdistrict, Central Mamuju district in Islamic law and customary law. This research aims to determine the position of the mamose tradition in Topoyo village, Topoyo sub-district, Central Mamuju district in terms of customary law and Islamic law. This research is a type of field research that is descriptive qualitative where the researcher describes a phenomenon, object, and social setting which is then expressed in writing in narrative form. This research shows that the Mamose tradition has collective values ​​that can unite and embrace the community in a traditional ceremony. The Islamic values ​​that are awakened in the Mamose traditional ceremony are the values ​​of harmony, cooperation, and the value of togetherness.